Free and Moving Boundary Problems of Heat and Mass Transfer - Kanakadurga Devi, P; G. Naidu, V; Mamatha, K; Naresh, B (International Journal of Engineering and Technology, 2018)
Bisection method is used to solve a moving boundary problem. This moving boundary problem was solved by the maze of mathematical manipulations by several authors. The method of using bisection is simple as compared to the lengthy mathematical manipulation of other methods. The procedure of the paper is useful in other moving boundary problems of heat and mass transfer, including boundary value problems involving ordinary differential equations with unknown interval length.Â Â